551 The unheard voices of clinical trials: A preliminary inquiry into the knowledge and sentiments of people experiencing homelessness (PEH) on clinical research - Bruno Baltazar (Journal of Clinical and Translational Science)
Objectives/Goals: The purpose of this pilot study is to conduct a survey interview to understand the knowledge and attitudes of people experiencing homelessness (PEH) toward clinical trial participation, provide insights for future engagement strategies, and begin bridging the gap between clinical researchers and this marginalized group. Methods/Study Population: A 14-question survey, developed in collaboration with the street medicine (SM) team at the University of Southern California and other key stakeholders in PEH research, was administered in a survey–interview style to PEH in SM’s East Side Los Angeles area of operations. The questions were designed to assess PEH’s knowledge and attitudes toward the significance of clinical research and their potential participation. No identifying information was collected. To ensure diversity in responses, the surveys were conducted in different SM healthcare providers’ areas of operations. The responses were then analyzed both quantitatively and qualitatively, taking into account the broader perspectives that PEH may have toward clinical trial research. Results/Anticipated Results: A total of 9 PEH were surveyed. When asked to share their thoughts on “clinical trials” (CTs), most described the need to travel on-site to a practitioner to be studied/tested. They indicated that they knew what CTs were and that the FDA’s official definition was easy to understand. Only one respondent reported being part of a diagnostic trial, and one declined to answer. Four respondents indicated a willingness to participate in a CT. Four answered “maybe” and one answered “no.” Of note, most believed that CTs have a positive impact, and only one responded that they think researchers do not maximize health benefits and minimize risk. Outside of the allowed answer choices, respondents also shared that there should be payment for participation in a CT, even if they don’t expect any. Discussion/Significance of Impact: The survey results could significantly influence the future of clinical research, guiding it to be better tailored to PEH’s unique circumstances, thereby potentially improving their participation rates. A key objective for the future will be to increase the sample size of the survey to improve the applicability and impact of the results.